Divulgação científica por meio do museu game ciência numa perspectiva sociocultural - NASCIMENTO, Genildo Viana do (2022)
Science museums are places markedly associated with the Scientific Dissemination, for assuming communicative contours that allow them to dialogue with society. In this approach, visitors are led to integrate the proposals of the Exhibition Discourse and mean them through their cognitive processes in a dialogical relationship with the exhibition. Among the various strategies that are placed in the expression of an Exhibition Discourse, we insert in this work the digital games as cultural tools capable of disseminating science, given their properties that characterize them as resources that promote motivation, decision-making, interactivity, overcoming challenges, etc. With this in mind, this work refers to the field of Science Popularization in the conception of a game museum as a non-formal educational space, with a focus on science teaching. Thus, the objective of this research focused on analyzing the Exhibition Discourse of the Game Science Museum, facing its curatorial constitution from the perspective of Science Education in a sociocultural context. This is a study with a qualitative approach of documentary typology, in which data collection followed supported by stages of the curatorial process, guided by the musealization processes. For the basis of the analysis were developed categories based on the assumptions of museum curatorship, reflected on the notion of Exhibition Discourse and the sociocultural aspect with the Theory of Mediated Action by James Wertsch. The categories were: selective valuation of objects; expographic resources and strategies; and educational actions. In view of this organization, the results of the research were discussed in three moments: in the first, we analyzed the historicity of consoles and games as artifacts to be incorporated into the collection of the Game Science museum, in which we prioritized the selective character of these objects due to their mediational properties, highlighting the cognitive aspects that stand out in the handling of these tools with a centralized look at the teaching of science; In the second moment we stopped thinking about the exhibition regarding its form and content, producing printed exhibition texts for the physical space of the exhibition and electronic texts of Scientific Dissemination for the digital space of the museum, to be inserted in its website. Thus, the planning of such expographic resources was described according to the possibilities of interaction and preservation of the museum objects; in the third moment we turned our attention to the Museological Activities, which were incorporated into the Exhibition Discourse on the bias of James Wertsch's Theory of Mediated Action, allowing us to think the dynamics of the exhibition, along with its objectives within the sociocultural aspect of learning. With this, four museological activities were developed and described, dealing respectively with the visitation to the museum's physical environment, game design for the evaluation of games from the collection itself, and Programming Logic with Scratch and the Code.org platform. These activities carry in themselves substantial elements possibly capable of awakening in visitors decision making, dialogicity, social interaction, critical positioning, reflection on the social impacts of science, etc. Such elements were mapped in the activities according to some properties of the Theory of Mediated Action, of which we highlight: the proposition of multiple simultaneous objectives; the exploration of irreducible tension (agents-acting-with-cultural-tools); and the use of materiality and situations of knowledge mastery and appropriation. Therefore, we consider that this study brings significant contributions to the teaching of science, especially thinking about the context of the schools of the basic municipal education network of the city of Bacabal/MA, where geographically the museum is inserted.